Anti-Thyroid Peroxidase Antibodies and Male Gender Are Associated with Diabetes Occurrence in Patients with Beta-Thalassemia Major - Giovanni M. Pes; Francesco Tolu; Maria P. Dore (Journal of Diabetes Research)
Background. Intensive transfusion schedule and iron-chelating therapy prolonged and improved quality of life in patients with β-thalassemia (β-T) major. However, this led to an increased risk of developing impaired glucose tolerance or diabetes. In this study we analyzed variables associated with the occurrence of impaired glucose tolerance or diabetes in patients with β-T major. Methods. 388 Sardinian patients were included. Age, gender, duration of chelation therapy, body mass index, and markers of pancreatic and extrapancreatic autoimmunity were analyzed. Results. Multiple logistic regression analysis showed that anti-thyroid peroxidase (TPO) antibodies (Ab) (OR = 3.36; p=0.008) and male gender (OR = 1.98; p=0.025) were significantly associated with glucose impairment, while the other variables were not. Ferritin levels were significantly higher in TPOAb positive compared to TPOAb negative patients (4870 ± 1665 μg/L versus 2922 ± 2773 μg/L; p<0.0001). Conclusions. In patients with β-T major a progressive damage of insulin-producing cells due to secondary hemosiderosis appears to be the most reasonable mechanism associated with glucose metabolism disorders. The findings need to be confirmed with additional well designed studies to address the question of whether TPOAb may have a role in the management of these patients.